A Meta-Analysis of the International Gender Wage Gap - Doris Weichselbaumer; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2003)
Since the early seventies, hundreds of authors have calculated gender wage differentials between women and men of equal productivity. Consequently, estimates for the gender wage gap have been published for the most diverse countries at different points in time. This metastudy provides a quantitative review of this vast amount of empirical literature on gender wage discrimination as it concerns differences in methodology, data, countries and time periods. We place particular emphasis on a proper consideration of the quality of the underlying study which is done by a weighting with quality indicators. The results show that data restrictions have the biggest impact on the resulting gender wage gap. Moreover, we are able to show what effect a misspecification of the underlying wage equation – like the frequent use of potential experience – has on the calculated gender wage gap. Over time, raw wage differentials world-wide have fallen substantially; however, most of this decrease is due to an increased labor market productivity of females.
Keywords: J31; J16; J71; 330; gender wage differential; meta-analysis; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Empirische Methode; Modell-Spezifikation; Welt